Correction: Essential role of hydride ion in ruthenium-based ammonia synthesis catalysts. Issue 8 (23rd June 2016) - Kitano, Masaaki; Inoue, Yasunori; Ishikawa, Hiroki; Yamagata, Kyosuke; Nakao, Takuya; Tada, Tomofumi; Matsuishi, Satoru; Yokoyama, Toshiharu; Hara, Michikazu; Hosono, Hideo
Abstract : Correction for 'Essential role of hydride ion in ruthenium-based ammonia synthesis catalysts' by Masaaki Kitano et al., Chem. Sci., 2016, 7, 4036-4043.